Energy Efficient Routing Protocol in Mobile-Sink Wireless Sensor Networks - Ming Chen; Xumin Xu; Shaohui Zhang; Guofu Feng (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Energy consumption phenomenon has always been noticed in sink-based wireless sensor networks. This paper explored an energy efficient routing protocol with a mobile sink based on the shortest path data transmission mode. According to the position of the sink node and the common nodes' ID in the network, we can calculate the coordinate value of each node in the wireless sensor network. By comparing the coordinate values to choose the shortest path to forward the data was our key method in this paper. Simulation results showed that this method can prolong the lifetime of the network, and improve the energy utilization ratio of the nodes. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1640